Scalable ion concentration polarization dialyzer for peritoneal dialysate regeneration - Wonseok Kim; Seongjun Hong; Kihong Kim; Sunhwa Lee; Dong Ah Shin; Seung Hee Yang; Jeongeun Lee; Kyunghee Kim; Kyoung Jin Lee; Woo Sang Cho; Hajeong Lee; Dong Ki Kim; et al. (Journal of Nanobiotechnology)
Abstract A wearable artificial kidney (WAK) stands poised to offer dialysis treatment with maximal temporal and spatial flexibility for end-stage renal disease (ESRD) patients, while portability has not yet been achieved due to difficulties in portable purification. The ion concentration polarization (ICP), one of the nanoelectrokinetic phenomenon, has garnered substantial attention in the realm of portable purification applications, owing to its remarkable capacity for charge separation. In this work, scalable ICP dialyzer with 10,000-fold increase in throughput, was applied for peritoneal dialysate regeneration. First, the mechanism underpinning dialysate purification was corroborated based on micro-nanofluidics. Simultaneously, the electrochemical reactions utilized the complete decomposition of uncharged toxin (urea), achieving approximately 99% clearance, while the ICP phenomenon promoted the removal of positively charged toxin (creatinine), achieving approximately 30% clearance. Second, 3-D scalable ICP dialyzer was developed with a creation of micro-nanofluidic environment inside. Throughput scalability was demonstrated up to 1 mL/min with average approximately 30% toxins clearance. Ultimately, the 3-D ICP dialyzer was applied to assist peritoneal dialysis (PD) using a bilateral nephrectomy rat model. We demonstrated that regenerated dialysate successfully reduced in vivo toxicity, with average toxins removal ratio of approximately 30% per cycle. We believe that the integration of this scalable ICP dialyzer into the WAK holds tremendous potential for substantially enhancing the quality of life for individuals with ESRD. Graphical abstract